Coexistence of hypertension and antinuclear antibodies: High blood pressure as a potential risk factor for autoimmunity (Annals of Medical Research, 2025)
Aim: Hypertension (HT) is characterized by endothelial damage, vascular wall stress, and inflammation, potentially fostering autoantibody production. The prevalence of antinuclear antibodies (ANAs), common autoantibodies associated with systemic autoimmune diseases, remains unclear in non-autoimmune conditions like HT. This study aimed to investigate the presence of ANAs (anti-dsDNA, anti-ENA, anti-Hep-2 nucleus) in HT patients and compare these findings with healthy individuals.Materials and Methods: This experimental case-control study included 32 hypertensive patients (7 men, 25 women; age 48.9 ± 6.6) and 32 age- and gender-matched healthy controls (7 men, 25 women; age 48.0 ± 5.2). HT status was self-reported based on prior diagnoses. ANAs, including anti-dsDNA, anti-ENA, and anti-Hep-2 nucleus antibodies, were measured using validated ELISA kits.Results: Body mass index (BMI) and ages were comparable between groups (p > .05). Median ANA index values and positivity rates (%) for hypertensive and healthy groups were: anti-dsDNA [1.25 (59.4%) vs. 0.8 (28.1%)], anti-ENA [0.92 (46.9%) vs. 0.64 (21.9%)], and anti-Hep-2 nucleus [0.93 (43.8%) vs. 0.84 (18.8%)]. All three ANA tests showed significantly higher ANA levels and positivity rates in the hypertensive group compared to controls (p < 0.05).Conclusion: Our findings indicate higher ANA levels and positivity rates in individuals with HT compared to healthy controls, suggesting a potential link between HT and autoantibody production. Further long-term prospective studies are needed to determine the clinical significance of this elevated ANA frequency and the potential role of these antibodies in the development of autoimmune diseases.
Keywords: Hypertension; Antinuclear antibody; dsDNA; ENA